An overview of reclaimed water reuse in China - Yi, Lili; Jiao, Wentao; Chen, Xiaoning; Chen, Weiping (Journal of environmental sciences (China), 2011)
China is facing severe water problems including scarcity and pollution which are now becoming key factors restricting developments. Creating an alternative water resource and reducing effluent discharges, water reuse has been recognized as an integral part of water and wastewater management scheme in China. The government has launched nationwide efforts to optimize the benefits of utilizing reclaimed water. This article reviewed the water reuse activities in China, including: (1) application history and current status; (2) potentials of reclaimed water reuse; (3) laws, policies and regulations governing reclaimed water reuse; (4) risks associated with reclaimed water reuse; (5) issues in reclaimed water reuse. Reclaimed water in Beijing and Tianjin were given as examples. Suggestions for improving the efficiencies of reusing urban wastewater were advanced. Being the largest user of reclaimed wastewater in the world, China's experience can benefit the development of water reuse in other regions.